DIAGNOSTIK KESULITAN BELAJAR MATEMATIKA SISWA PADA MATERI FPB & KPK KELAS V SD NEGERI - Asisah Nur Fariana; Nur Muhlifa Nahli; Herdiawal Herdiawal; Anis Fuadi; Nurjannah Nurjannah (LP2M Institut Agama Islam (IAI) Muhammadiyah Sinjai, 2022)
This study aims to diagnose students' difficulties in understanding and using the principle concepts in the FPB and KPK materials. This research uses a qualitative research type. The subjects of this research are fifth grade students at SDN 2 Balangnipa in the 2021/2022 academic year. Subject selection was based on mathematical ability and the considerations given by the fifth-grade teacher. The method used in this study was the method of documentation, tests and interviews. The results and conclusions of the research obtained include the types of student difficulties in the FPB and KPK materials are (1) Students have difficulty learning mathematics in the material about finding FPB and KPK scores (2) Lack of interest and enthusiasm for studying mathematics in addition to the limited mathematics learning tools available. used by educators